The priesthood of all believers : a re-statement - Borman, John (Rhodes University, Faculty of Divinity, Department of Divinity, 1966)
From Preface: In this age of ecumenical discussion it has becone necessary for all Christian communions to examine afresh their traditional beliefs. This has frequently led to restatement and reformulation of such traditional beliefs. It has also driven us back to seek new light from the Biblical sources. It seemed that such a re-examination of the traditional doctrine of the priesthood of all believers was necessary so that those who claim to hold it know what they hold, and so that those who do not may know what it is that their fellow-Christians believe, and why. This was the first reason for this study.
Keywords: Priesthood, Universal; Christian life; Church renewal; Ministry and Christian union